Assignment of Weight-Based Antibody Units for 13 Serotypes to a Human Antipneumococcal Standard Reference Serum, Lot 89-S(F) - Quataert, Sally A. (American Society for Microbiology, 2004)
Weight-based immunoglobulin G (IgG), IgM, IgA, and total Ig antibody assignments were made to human antipneumococcal standard reference serum lot 89-S, also known as lot 89-SF, for Streptococcus pneumoniae capsular polysaccharide (PnPs) serotypes 2, 6A, 8, 9N, 10A, 11A, 12F, 15B, 19A, 17F, 20, 22F, and 33F, as well as for C-polysaccharide (C-Ps), extending the standard's usefulness for pneumococcal vaccine evaluation beyond the original serotype 1, 3, 4, 5, 6B, 7F, 9V, 14, 18C, 19F, and 23F assignments (S. A. Quataert, C. S. Kirch, L. J. Quackenbush Wiedl, D. C. Phipps, S. Strohmeyer, C. O. Cimino, J. Skuse, and D. V. Madore, Clin. Diagn. Lab. Immunol. 2:590-597, 1995). The additional 14 assignments were determined using an equivalence of absorbance method with an anti-PnPs serotype 6B reference enzyme-linked immunosorbent assay (EIA). To assure accuracy, anti-PnPs EIA for serotype 14 antibodies, a previously assigned serotype, was performed concurrently. This method assures consistency of the new microgram-per-microliter assignments with previous antiserotype assignments to lot 89-S. The sum of the experimentally derived isotype assignments for anti-PnPs serotypes in lot 89-S agrees well with the separately determined total Ig assignment for each serotype. The lot 89-S assignments for serotypes 1, 5, 6B, 14, 18C, 19F, and 23F were used for pneumococcal conjugate vaccine clinical trial evaluation and to generate data in efficacy trials where serological correlates for protection have been proposed. The assignment of antibody concentrations to additional pneumococcal serotypes in this reference reagent facilitates the consistent and accurate comparison of serum antibody concentrations across clinical trials.